Methods in Biotechnology - Hans-Peter Schmauder [ editor ] (Taylor & Francis, 1997)
Provides a grounding in the experimental techniques applicable to the discipline of biotechnology. The introductory section in the text describes procedures for analysis of inorganic and organic materials, strain maintenance and fundamental experiments in gene manipulation. Other chapters deal with fermentation techniques, purification methods for substances of interest, preparation of microbial sensors and the demonstration of oil degradation by bacteria. The final chapter deals with statistical planning of experiments and scale-up methods.